Physical and Mechanical Properties of Cemented Ash-Based Lightweight Building Materials with and without Pumice. (2nd April 2018) - Doğan-Sağlamtimur, Neslihan; Güven, Adnan; Bilgil, Ahmet
Abstract : Pumice, cements (CEM I- and CEM II-type), waste fly and bottom ashes (IFA, GBA, and BBA) supplied from international companies were used to produce lightweight building materials, and physical-mechanical properties of these materials were determined. Axial compressive strength (ACS) values were found above the standards of 4 and 8 MPa (Bims Concrete (BC) 40 and 80 kgf/cm 2 class) for cemented (CEM I) pumice-based samples. On the contrary, the ACS values of the pumice-based cemented (CEM II) samples could not be reached to these standards. Best ACS results (compatible with BC80) from these cemented lightweight material samples produced with the ashes were found in 50% mixing ratio as 10.6, 13.2, and 20.5 MPa for BBA + CEM I, GBA + CEM II, and IFA + CEM I, respectively, and produced with pumice were found as 8.4 MPa (same value) for GBA + pumice + CEM II (in 25% mixing ratio), BBA + pumice + CEM I (in 100% mixing ratio), and pumice + IFA + CEM I (in 100% mixing ratio), respectively. According to the results, cemented ash-based lightweight building material produced with and without pumice could widely be used for constructive purposes. As a result of this study, an important input to the ecosystem has been provided using waste ashes, whose storage constitutes a problem.